Visible-Light-Enabled Radical Alkynylborylation of Activated Alkenes - Zhu, Congjun; Yao, Shunruo; Xie, Jin (Synthesis, 2023)
A photoredox-catalyzed protocol for performing radical difunctionalization of alkenes using N-heterocyclic carbene (NHC) boranes and alkynyl bromines is described. The alkynylborylation difunctionalization reaction involves photoredox generation of boryl radical, with subsequent radical addition to the double bond followed by the capture of alkynyl bromide to form a C–C bond. This method features mild reaction conditions, remarkable chemoselectivity, broad substrate scope and good to excellent yields (up to 89%). The modification of coumarin derivatives indicates that this approach can provide a useful route for the synthesis of complex alkynylborylated products.
Keywords: photoredox catalysis; N-heterocyclic carbene boranes; alkynyl bromides; radical reaction; difunctionalization